Kinetics, Isotherms and Thermodynamics of the Adsorption of Lead(II) Ions onto Porous Mono-Sized Microspheres Possessing Imidazole Functional Groups - Ali Kara; Ali Tuncel (Adsorption Science & Technology, 2011)
A modified two-step seeded polymerization was used for the preparation of porous mono-sized microspheres of poly(ethylene glycol dimethacrylate- co -1-vinylimidazole) [poly(EGDMA- co -VIM)] of 7 μm in size. The specific surface area and the EGDMA/VIM molar ratio of the microspheres were determined as 64.5 m 2 /g and 1.5:1.0 mol/mol, respectively. The adsorption of Pb(II) ions from aqueous solution onto the porous mono-sized poly(EGDMA- co- VIM) microspheres was examined. The maximum adsorption capacities of the microspheres towards Pb(II) ions were determined as 21.74, 30.52, 49.23 and 56.48 mg/g at 293 K, 303 K, 318 K and 338 K, respectively. The dynamic and equilibrium adsorption behaviours of the system were adequately described by the pseudo-second-order kinetic model and the Langmuir isotherm, respectively. The apparent activation energy was determined as 6.212 kJ/mol, which is characteristic of a chemically controlled reaction. The values of E fe obtained from the Dubinin–Radushkevich equation in the non-linear form were 9.153 kJ/mol at 293 K, 10.34 kJ/mol at 303 K, 10.18 kJ/mol at 318 K and 10.91 kJ/mol at 333 K, thereby indicating that the adsorption of Pb(II) ions onto the porous monosized poly(EGDMA- co -VIM) microspheres occurred via a chemical process at all the temperatures studied. Various thermodynamic parameters, such as the Gibbs' free energy change (ΔG 0 ), the standard enthalpy change (ΔH 0 ) and the standard entropy change (ΔS 0 ) were also determined. The thermodynamic parameters obtained indicated that the adsorption process was endothermic in nature. These results demonstrate that the material studied could be used as a purifier for the removal of Pb(II) ions from water and wastewater.